COLOR PHASE MODULATION FOR LI-FI COMMUNICATION - D Satyanarayana; Ashjan; Modhi; Amal; Fawtam; Mithaa (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The need of radio spectrum in wireless communication has crossed with the requirements of the current society. There are few solutions to the radio spectrum insufficiency. One of the alternative solutions is the communication with visible light spectrum, such as Light Fidelity. The paper has a new method for visible light communication called Color Phase Modulation (CPM). The proposed modulation method is simulated and presented the results.